Online to Offline Learning; Transition to New Normal Education - Firman Firman; Arlinda Puspita Sari; Hadira Hadira (SAINTIFIK, 2023)
This qualitative research aims to examine the transition from online learning to offline Face-to-Face Instruction. The research was conducted at SMAN 2 Majene from August to November 2021. Data collection was carried out in three stages. The first stage was distributing questionnaires to 63 students. The second stage was the observation of learning in classroom. The third stage was in-depth interviews with 9 students using interview guidelines. This research was approved by the Principal of SMAN 2 Majene and all participants have expressed their willingness to be research respondents. Open questionnaire data and interview results were analyzed using Miles and Huberman’s qualitative data analysis techniques, which include data presentation, data reduction, and drawing conclusions, observational data are summarized and presented in tabular form. The results showed that (1) students are more excited and motivated to learn when face-to-face instruction is implemented; (2) Students experience social awkwardness when meeting friends at school. (3) Students struggle to actively engage in learning; and (4) Students have found it difficult to break their online study habits. The results of this study were expected to be taken into consideration for teachers in designing learning in the new normal period.